2001
DOI: 10.4315/0362-028x-64.4.503
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination Occurring on Lamb Carcasses Processed in the United States

Abstract: Lamb carcasses (n = 5,042) were sampled from six major lamb packing facilities in the United States over 3 days during each of two visits (fall or winter, October through February; spring, March through June) in order to develop a microbiological baseline for the incidence (presence or absence) of Salmonella spp. and for populations of Escherichia coli after 24 h of chilling following slaughter. Samples also were analyzed for aerobic plate counts (APC) and total coliform counts (TCC). Additionally, incidence (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 19 publications
1
17
2
Order By: Relevance
“…Lower level of aerobic plate count in this study was much lower than previous studies [2,[35][36][37]. However, the microbial contamination level of slaughterhouse and retail shops were higher as compared to reports from developed countries and our results do not conform to EU specifications [38,39].…”
Section: Discussioncontrasting
confidence: 56%
“…Lower level of aerobic plate count in this study was much lower than previous studies [2,[35][36][37]. However, the microbial contamination level of slaughterhouse and retail shops were higher as compared to reports from developed countries and our results do not conform to EU specifications [38,39].…”
Section: Discussioncontrasting
confidence: 56%
“…A low prevalence of the pathogen was found on fleece (0.25%) and in faeces (0.25%). Previous studies have reported Salmonella on 4.3% of pre-evisceration lamb carcasses (Kalchayanand et al, 2007) and 1.5% on chilled carcasses (Duffy et al, 2001). The pathogen has been detected in 0.1-11% of sheep faeces (Davies et al, 2004;Milnes et al, 2008;Zweifel, Zychowska, & Stephan, 2004) and on 7.8-14.4% of fleece (Kalchayanand et al, 2007;Small et al, 2002).…”
Section: Visitmentioning
confidence: 92%
“…In the latter studies it was noted that bacterial distribution on carcasses was not uniform and the carcasses selected for sampling could have a big influence on the TVC's and Enterobacteriaceae counts recorded. Australia and the US have successfully incorporated chilling into a HACCP plan (Duffy et al, 2001;Sumner et al, 2003). In Australia, three baseline studies over 11 years showed an improvement in the microbiological quality of beef carcasses and this was attributed in part to investment in chilling systems (Philips, Jordan, Morris, Jenson, & Sumner, 2006).…”
Section: Visitmentioning
confidence: 98%
“…In metropolitan Washington, DC, for example, 130 of 184 (71%) packages of chicken sold at retail outlets contained C jejuni or C coli, followed by 4% of 172 turkey packages and < 2% of pork and beef packages. 42 Another US study 89 of more than 2,000 lamb carcasses from 6 large processing plants showed that < 1% were contaminated with C jejuni or C coli. In an English study 3 of nearly 500 retail specimens, chicken meat had the highest contamination rate (83%); however, the majority of lamb liver (73%), pork liver (72%), and beef liver (54%) was also contaminated.…”
Section: Food and Water Sourcesmentioning
confidence: 99%